2015
DOI: 10.1016/j.bbrc.2014.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the 15-kDa selenoprotein led to cytoskeleton remodeling and non-apoptotic membrane blebbing through a RhoA/ROCK pathway

Abstract: The 15-kDa selenoprotein (Sep15) has been implicated in etiology of some types of cancer. Herein, inducible RNAi cell lines were established and cell morphology and motility were analyzed. The majority of Sep15-deficient cells (>95%) formed membrane blebs in a dynamic manner. Blebbing cells transformed cell morphology from a normal flat spindle shape to a spherical morphology. In blebbing cells, actin fibers moved to the cell periphery, covering and obscuring visualization of α-tubulin. Bleb formation was supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
0
25
1
1
Order By: Relevance
“…This is in line with our finding that RhoA and RhoB controlled different aspects of 3D amoeboid leukaemia cell migration, with RhoA being important for cell rear retraction, while RhoB controlled membrane blebbing. This contrasts with previous studies that have suggested a role for RhoA in cell membrane blebbing (Gadea et al , ; Godin & Ferguson, ; Cartier‐Michaud et al , ; Tozluoglu et al , ; Takahara et al , ; Bang et al , ; Aoki et al , ). However, in most of these studies, experimental methods (e.g.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This is in line with our finding that RhoA and RhoB controlled different aspects of 3D amoeboid leukaemia cell migration, with RhoA being important for cell rear retraction, while RhoB controlled membrane blebbing. This contrasts with previous studies that have suggested a role for RhoA in cell membrane blebbing (Gadea et al , ; Godin & Ferguson, ; Cartier‐Michaud et al , ; Tozluoglu et al , ; Takahara et al , ; Bang et al , ; Aoki et al , ). However, in most of these studies, experimental methods (e.g.…”
Section: Discussioncontrasting
confidence: 82%
“…However, in most of these studies, experimental methods (e.g. non-specific drug-based inhibition) did not provide clear indications as to which Rho family member is responsible for effects and in other cases, blebbing function was inferred from gross cell morphology rather than direct visualization of blebbing per se (Gadea et al, 2007;Pinner & Sahai, 2008;Godin & Ferguson, 2010;Cartier-Michaud et al, 2012;Tozluoglu et al, 2013;Takahara et al, 2014;Bang et al, 2015;Aoki et al, 2016). In any case, our finding that depletion of RhoB impaired membrane blebbing in four distinct cell models of different origin shows that RhoB is critical for membrane blebbing under a variety of conditions.…”
Section: Discussionmentioning
confidence: 99%
“…When the cells grew to a confluent state, each clone was transferred to a single well in a 24-well plate and allowed to expand. The cells were then analyzed for the expression of mouse Sps1 , mouse Glrx1 , and human Glrx1 by quantitative PCR (qPCR) as previously described [21]. Briefly, total RNA was isolated from each cell line using TRIzol®.…”
Section: Methodsmentioning
confidence: 99%
“…The vector (pcDNA4/TO.mSPS1Rescue) was transfected into F9/shSPS1 cells and the transfected cells were selected in the presence of 400 μg/ml Zeocin ™ . Cells were then analyzed by qPCR for the expression of endogenous mouse Sps1 , mouse Glrx1 , and rescue mouse Sps1 as previously described [21]. Briefly, total RNA was isolated from each cell line, first-strand cDNA was synthesized, and the cDNA was subjected to PCR using the following specific primer sets: for endogenous mouse Sps1 , mSPS1-F and mSPS1-R; for mouse Glrx1 , mGlrx1-F and mGlrx1-R; for rescue mouse Sps1 , mSPS1 (Rescue)-F and mSPS1 (Rescue)-R; and for mouse Actb , ACTB-F and ACTB-R.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation